Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Keterampilan Berpikir Komputasional pada Pembelajaran IPA Siswa SMP - Ningrum, Dina Dwi Septya; Supeno, Supeno; Rusdianto, Rusdianto (Universitas Indraprasta PGRI Jakarta, 2024)
This study aims to examine the effect of using a guided inquiry learning model on the computational thinking skills of junior high school students in science learning. The research was conducted with a quantitative approach through quasi-experimental research design. The subjects studied were students of SMP N 7 Jember, each consisting of 36 students including class VII B as a control class (applying a direct learning model) and VII F as an experimental class (applying a guided inquiry learning model). Data collection was carried out through the provision of computational thinking skills tests as many as 7 essay questions. Problems are developed based on indicators of computational thinking skills (decomposition, pattern recognition, abstraction, and algorithms). The results of the independent sample t-test of the control class and experimental class obtained a value of Sig. (2-tailed) 0.000 smaller than the significance level of 0.05. Based on the test criteria Independent sample t-test, it can be concluded that there is a significant comparison between pretest and posttest values in the control class and experimental class. Next, the right-party t-test was carried out with the results of a calculated value of 22.210 greater than ttable 1.996 with a significance level of 0.05, indicating a significant difference between the average scores of students' computational thinking skills in the control class and the experimental class. This shows that learning using a guided inquiry model is effective in improving the computational thinking skills of junior high school students in science learning.